Development and Prospect of Esophageal Tissue Engineering - Xu, Rui; Fang, Xinnan; Wu, Shengqian; Wang, Yiyin; Zhong, Yi; Hou, Ruixia; Zhang, Libing; Shao, Lei; Pang, Qian; Zhang, Jian; Cui, Xiang; Zuo, Rongyue; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Currently, patients with esophageal cancer, especially advanced patients, usually use autologous tissue for esophageal alternative therapy. However, alternative therapy is often accompanied by serious complications such as ischemia and leakage, which seriously affect the prognosis of patients. Tissue engineering has been widely studied as one of the ideal methods for the treatment of esophageal cancer. In view of the complex multi-layer structure of the natural esophagus, how to use the tissue engineering method to design the scaffold with structure and function matching with the natural tissue is the principle that the tissue engineering method must follow. This paper will analyze and summarize the construction methods, with or without cells, repair effects of single-layer scaffold and multi-layer scaffold. Especially in the repair of full-thickness and circumferential esophageal defects, the flexible design method and the binding force between layers of scaffold are very important. In short, esophageal tissue engineering technology has broad prospects and plays a more and more important role in the treatment of esophageal diseases.